Determining the optimal initial dose for Japanese patients with nocturnal polyuria using an initial dose of desmopressin 50 μg. Issue 3 (8th February 2023) - Kurose, Hirofumi; Komiya, Keisuke; Ogasawara, Naoyuki; Ueda, Kosuke; Chikui, Katsuaki; Nishihara, Kiyoaki; Nakiri, Makoto; Matsuo, Mitsunori; Suekane, Shigetaka; Igawa, Tsukasa
Abstract: Objective: There is no consistent opinion on the optimal initial dose of desmopressin for patients with nocturnal polyuria. Over a period of 12 weeks, we investigated the safety and efficacy of an initial dose of 50 μg of desmopressin for elderly men. Methods: Eighty patients (mean age: 78.8 years) were started on an initial dose of 50 μg of desmopressin for nocturia associated with nocturnal polyuria. Safety and efficacy were evaluated after 1, 4, and 12 weeks using a frequency‐volume chart, Athens Insomnia Scale, Patient Global Impression of Improvement scale, physical examination, blood tests, and a body composition analyzer. Results: Along with reduction in the frequency and volume of night‐time urination, improvements in hours of undisturbed sleep, nocturnal polyuria index, and International Prostate Symptom Score, and Overactive Bladder Symptom Scores on quality of life measures were also observed. Hyponatremia was observed in 15 patients (18.7%). However, only 5.0% of patients had hyponatremia after the dose was reduced to 25 μg, and the continuation rate at 12 weeks was high at 87.5%. Age and other physical factors, such as body mass index, body water content, body fat mass, and muscle mass were not significant predictors of adverse events. Conclusions: Our study suggests that an initial dose of 50 μg is more effective than a uniformly minimum dose based on factors such as age and physique. Furthermore, a high continuation rate can be achieved by appropriately reducing the dose, if adverse events occur.